2005
DOI: 10.1002/cphc.200500167
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Biodegradable Polymer Nanofibers Displaying Superparamagnetic Properties

Abstract: Superparamagnetic polymer nanofibers intended for drug delivery and therapy are considered here. Magnetite (Fe3O4) nanoparticles in the diameter range of 5-10 nm were synthesized in aqueous solution. Polymer nanofibers containing magnetite nanoparticles were prepared from commercially available poly(hydroxyethyl methacrylate), PHEMA, and poly-L-lactide (PLLA) by the electrospinning technique. Nanofibers with diameters ranging from 50 to 300 nm were obtained. Nanofibers containing up to 35 wt % magnetite nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…The saturation magnetization values for MC-PCL-M 1 , MC-PCL-M 3 , and MC-PCL-M 6 were found as 1.02, 2.07, and 3.78 emu/g, respectively, clearly dependent on the values of Fe 3 O 4 nanoparticles incorporation in the hydrogel structure [64]. We can see that the saturation magnetization (Ms) of the samples increases when the concentration of magnetite increases in the polymeric matrices.…”
Section: Analysis Of Magnetization Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…The saturation magnetization values for MC-PCL-M 1 , MC-PCL-M 3 , and MC-PCL-M 6 were found as 1.02, 2.07, and 3.78 emu/g, respectively, clearly dependent on the values of Fe 3 O 4 nanoparticles incorporation in the hydrogel structure [64]. We can see that the saturation magnetization (Ms) of the samples increases when the concentration of magnetite increases in the polymeric matrices.…”
Section: Analysis Of Magnetization Propertiesmentioning
confidence: 90%
“…Figure 10 shows the magnetization curves of the MC-PCL-M 1,3,6 hydrogel films measured at 300 K. The magnetization curves showed that the MC-PCL-M 1,3,6 hydrogels were superparamagnetic with no hysteresis and coercivity at room temperature. This characteristic property belongs to superparamagnetic nanoparticles that the thermal fluctuations are sufficient to prevail the anisotropic energy barrier [64,65].…”
Section: Analysis Of Magnetization Propertiesmentioning
confidence: 99%
“…In this way, materials that include fibers of poly(hydroxyethylmethacrylate) (PHEMA) or PLA have been recently prepared by the electrospinning technique. [73] Their potential significance to various applications in medicine, especially for accumulation of the delivered drug in a precise target area, relies on their superparamagnetic properties and their ability to release the transported drug. In the previous paragraphs we have illustrated recent examples of bionanocomposites designed and developed for artificial biological tissue applications, bone implants in particular, frequently involving collagen, PLA, and other related biopolymers.…”
Section: Bionanocomposites In Life Sciencesmentioning
confidence: 99%
“…In such materials different types of polymers including natural polymers, biopolymers and synthetic polymers, have been combined with magnetic nanoparticles (MNPs) including iron oxide (magnetite) (Fe3O4) [60,[104][105][106], maghemite (γ-Fe2O3) [107][108][109], cobalt (Co) [110], nickel (Ni) [111], iron-platinum (FePt) [112,113] NPs etc. From all the above, iron oxide NPs have been the most widely studied due to their biocompatibility, nontoxicity, and stability and are, by far, the most commonly employed MNPs in biomedical applications [114].…”
Section: Electrospun Magnetoactive Nanocomposites In Tissue Engineeringmentioning
confidence: 99%